Assessment of Practices in Integrating Environmental Education in the Teacher Education Program - Rebecca Rosario O. Bercasio (RIRAI Publisher, 2021)
The study aimed to assess the mainstreaming of environmental education in the Teacher Education curriculum. It used descriptive research design using qualitative approaches. Data were gathered using a rubric, documentary analysis, class observations, focus group discussion, and interview. Respondents and informants consisted of faculty-implementers, students, officials and administrative personnel. Each class in the different disciplines was observed by three class observers. The focus group discussion involved 35 students and the informal interview involved randomly selected class observers and key persons involved in the implementation of the project. Three dimensions were considered such as programmatic practices, organizational practices and context-specific practices. Assessment reveals the good practices in programmatic practices in terms of needs assessment and program design, in organizational practices in terms of governance, and context specific practices in terms of instructional materials development, delivery of the lesson, interaction with students, and assessment. Good practices serve as enabling factors for the successful mainstreaming of environmental education in the Teacher Education curriculum. Recommendations are provided to sustain the good practices and address those needing improvement.